Autism Treatment from Acupuncture Perspective - Liu, Jing; Xiaoqing, Zeng; Yao, Ping (North American Journal of Medicine and Science, 2018)
Although acupuncture has been used in the treatment of autism for many years, almost no formal clinical trials have been devoted to confirm the effectiveness of the acupuncture for the disease in the western countries, where a big population of children and family have been suffering from the shortage of effective therapy. This review is to summarize the reports from about 20 clinical trials of acupuncture for autism in the last decade in China. The results of these reports suggested that acupuncture may be a potentially valuable approach in treating autism. Around 80% symptom improvements were stated in most of the studies. The reports also demonstrated that acupuncture may enhance the efficacies of conventional therapies for autism, such as behavior rehabilitation therapy. It was suggested that the effects of acupuncture for autism may be partially related with its effects on anti-inflammation and on the modulation of the brain signal conductivity, supported by the research including fMRI. A concept of transcranial electrical acupuncture stimulation (TEAS) is proposed. Compared with the conventional acupuncture technique, TEAS is hypothesized to target directly on the brain lesions of autism through modulating hyperpolarized or depolarized neurons of the brain, in order to improve the pathological status of autism. Clinical trials are needed to approve the proposal in the future.